2018
DOI: 10.7150/jca.26897
|View full text |Cite
|
Sign up to set email alerts
|

LINC00852 Promotes Lung Adenocarcinoma Spinal Metastasis by Targeting S100A9

Abstract: Background: Lung adenocarcinoma has a strong tendency to develop into bone metastases, especially spinal metastases (SM). Long noncoding RNAs (lncRNAs) play critical roles in regulating several biological processes in cancer cells. However, the mechanisms underlying the roles of lncRNAs in the development of SM have not been elucidated to date.Methods: Clinical specimens were collected for analysis of differentially expressed lncRNAs. The Kyoto Encyclopedia of Genes and Genomes (KEGG) was used to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…24,25 Until now, only one study has been conducted on linc00852, which promote lung adenocarcinoma progression and spinal metastasis by activating MAPK pathway. 26 In this study, we have proven that exosomal linc00852 plays as a pivotal identified intercellular messenger in osteosarcoma. Exosomes are not only a cell-cell communication regulator but also an important mediator in the process of vascular remodeling, playing a mediating role in tumor microenvironment and promoting tumor metastasis.…”
mentioning
confidence: 76%
“…24,25 Until now, only one study has been conducted on linc00852, which promote lung adenocarcinoma progression and spinal metastasis by activating MAPK pathway. 26 In this study, we have proven that exosomal linc00852 plays as a pivotal identified intercellular messenger in osteosarcoma. Exosomes are not only a cell-cell communication regulator but also an important mediator in the process of vascular remodeling, playing a mediating role in tumor microenvironment and promoting tumor metastasis.…”
mentioning
confidence: 76%
“…In our study, through transcriptomics-based screening, we found that the 13 identified lncRNAs exhibited close interactions with genes in the blue module. Studies have revealed that AATBC (Zhao et al, 2015), ADAMTSL4-AS1 (Annunziato et al, 2019), EPB41L4A-AS1 (Liao et al, 2019), MIA-RAB4B (Thean et al, 2017), MIR4697HG (Zhang et al, 2017a), GAS5 (Ni et al, 2019), SNHG12 (Tamang et al, 2019), MSX2P1 (Qiao et al, 2018), and LINC00852 (Liu et al, 2018b) are related to tumorigenesis and tumor progression in multiple cancers, such as bladder, breast, colorectal, and ovarian. Apart from the nine lncRNAs identified in biological experiments, LOC254896 (Singh et al, 2018), LINC01000 (Mitchell et al, 2017), LINC00893 (Li et al, 2019a), and LINC00537 (Li et al, 2017b) were also reported to be significantly differentially expressed between diseased and normal tissues in some transcriptional profiling analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Liu P et. al indicated that LINC00852 promotes lung adenocarcinoma spinal metastasis by targeting S100A9 [37]. Although lncRNAs have played an emerging role in bone metastasis from other cancers, there are no studies assessing serum lncRNAs in cancer patients with bone metastasis.…”
Section: Discussionmentioning
confidence: 99%